TYUTORLÍQ ISKERLIGINIŃ ÁYYEMGI RIMGE KIRIP KELIWI HÁM RAWAJLANÍW TÁRIYXÍ - Begaliev, N.Q. (SCIENCE and SOCIETY, 2023)
This article analyzes the introduction and development of tutoring activity in the Ancient Roman Empire. The development of the tutoring activity in the Antiquity period, its place and importance in the Ancient Roman education system have been extensively analyzed.
Keywords: tutor; conception; education; university; pedagogue; Antique time; philosopher; academy; logic; rhetoric; politics; hellenism; empire